Transcriptional modulation of skin cells using liganded immodulin peptides: Liganded immodulins for skin - Mascarenhas, Desmond D.; Patel, Bhaumik; Ravikumar, Puja; Amento, Edward; Bhargava, Ajay (Cellular and Molecular Biology, 2025)
Immodulins are synthetic peptides that efficiently utilize iron-mediated cellular uptake, importin-mediated nuclear translocation and binding to retinoid X receptor to mediate transcriptional effects. The possible use of side-chain derivatized immodulins (SCDI) as tunable therapeutic agents is explored in this work. Rat biodistribution studies show that, when applied transdermally to rats using a nanoemulsion, immodulin peptides rapidly partition to skin tissue resulting in a 9X enrichment in skin relative to plasma, even at skin locations distant from the site of application. We show that optimized side-chain derivatization of immodulins with selected ligands of RXR heterodimeric partners can stimulate by one to three orders of magnitude: [a] CD169+CCL22+ macrophage differentiation (RARα/β ligand); [b] IL-19, IL-22 and IL-24 production by HaCaT keratinocytes (RARγ agonist); and [c] FGF7/KGF-1, TGFβ and COL1A1 by dermal fibroblasts (partial PPARγ ligand); all p<0.01. Differentiated CD169+ macrophages, in turn, drive the conversion of FoxP3 CD4+Tcells into iTregs (>4-fold, p<0.01) while reducing IL-17 levels >4-fold (p<0.01). In addition, myoblast differentiation is stimulated >10X by a PPARα ligand (p<0.01). These processes resemble key features of paracrine circuitry in skin known to be involved in wound healing. Versatile SCDI scaffolds hold promise for the rapid and inexpensive development of safe, targeted, self-administered therapeutic agents for skin.